Phenanthrolines as Energy Transfer Photocatalysts for the E → Z Isomerization of Alkenes - Chen, Xiao-Bo; Zhang, Jia; Sun, De-Qun; Chen, Kun-Quan; Chen, Xiang-Yu (Synthesis, 2025)
Phenanthrolines have been widely employed as chelating ligands for transition metals. Herein, this study investigates the utility of substituted o-phenanthrolines as independent photosensitizers for the E → Z isomerization of alkenes. The findings underscore the versatility of o-phenanthrolines, providing a straightforward, metal-free, and cost-effective method for synthesizing Z-alkenes.
Keywords: phenanthrolines; photocatalysis; energy-transfer; E → Z isomerization; alkenes